PENGEMBANGAN HANDOUT BERGAMBAR DILENGKAPI PETA KONSEP PADA MATERI KINGDOM PROTISTA UNTUK SISWA SMA - Sandika, Rini; nerita, siska; Susanti, Diana (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ The goal of learning can obtain because of media of learning. Media is mediator than deliver a message or information which instructional purpose or contain a learning. There are many media that use by the teacher in teaching learning process. Each of media is that use by the teacher is media form. Media form is such a handout. Handout is something that given to the learners when the process of learning. The teacher can make a handout from several literature which have relevancy with basic competence that will obtained by the students. Based on the observation and interview that have been conducted in SMA N 1 Jujuhan that in this school do not use a handout in process of learning. And that school only use a LKS and book. The LKS have not picture with colour, and that picture only for several material.The purpose of this research to resulted a pictorial handout with mind map in Kingdom Protista material which valid and practical. This research is the development research that use model 4-D which have 4 step define step, design, develop and disseminate. The data of this research is primary data is the direct data that get from the lecturer, teachers, and students. The analysis data is descriptive analysis. The result of research that have been got is average validity by lecturer and teacher amount 84 %. The deserve a handout measure from same aspect a deserve content, language, presentation and graphic. The average praktikalitas by teacher amount 90,56 %. The practicality of handout measure by several aspect easy of emplaying, effective of the time and presentation. The average or praktikalitas students amount 87,65 % and measure by several aspect easy of emplaying, effective of the time and presentation. Based on that cases the conclusion is handout that resulted have been valid and very practical.